1997
DOI: 10.1021/jp962922n
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption Spectra of Nanocrystal Gold Molecules

Abstract: The optical absorption spectra of a series of nanocrystal gold moleculesslarger, crystalline Au clusters that are passivated by a compact monolayer of n-alkylthiol(ate)sshave been measured across the electronic range (1.1-4.0 eV) in dilute solution at ordinary temperature. Each of the ∼20 samples, ranging in effective core diameter from 1.4 to 3.2 nm (∼70 to ∼800 Au atoms), has been purified by fractional crystallization and has undergone a separate compositional and structural characterization by mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

109
1,132
5
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,300 publications
(1,252 citation statements)
references
References 37 publications
109
1,132
5
6
Order By: Relevance
“…Another important aspect of noble NPs, when dispersed in a dielectric matrix, is that their optical response strongly depends on their clustering tendency, namely the clusters size, shape and distribution [3,35,36], the interaction between them [7,37], but also on the host matrix dielectric function itself [11,[38][39][40][41].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Another important aspect of noble NPs, when dispersed in a dielectric matrix, is that their optical response strongly depends on their clustering tendency, namely the clusters size, shape and distribution [3,35,36], the interaction between them [7,37], but also on the host matrix dielectric function itself [11,[38][39][40][41].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…9 The proposed model can also explain the controversy about the metallic or insulating character of thiol-capped Au NPs. For NPs below 2 nm in size, several authors observe localized charge behavior 9,20,21 while recent studies showed the presence of free electrons. 14,15 According to our model ͑see Fig.…”
mentioning
confidence: 99%
“…Having determined R S independently from the SAXS data, we are now in a position to evaluate A (see Figure 4). Its average value is about A = 0.35, to be compared with the literature values of 0.6 − 2 for gold spheres [24][25][26] . …”
Section: Saxsmentioning
confidence: 61%